Spanglish - Brooks, James L.; Sakai, Richard; Ansell, Julie; Sandler, Adam; Leoni, Tea 1966-; Vega, Paz 1976-; Leachman, Cloris; Bruce, Shelbie; Steele, Sarah; Hyland, Ian; Luna, Victoria; Seale, John 1942-; et al. (Columbia Pictures Sony Pictures Home Entertainment, 2005)
When Flor and her daughter Christina come to the United States from Mexico, Flor gets a job as a maid at the home of successful chef John Clasky, his insecure wife Deborah, their two children, and Deborah's mother. When they move in with the Claskys for the summer, Flor discovers that life in a new country can be challenging in more ways than one.